Effect of deficit irrigation on yield and oil content of safflower seeds (Carthamus tinctorius L). (Damascus University Journal of agriculture sciences, 2024)
The research was conducted in Abi Jarash farm at the Faculty of Agriculture at Damascus University, located within the Damascus Water Basin, at latitude (32.3), longitude (36.18) and altitude above sea level (725) meters, during the 2019 season to study the effect of deficient irrigation on some quantitative and qualitative characteristics of a local variety From the safflower plant, and  know its response to drought conditions, five irrigation treatments were applied (full irrigation - stopping irrigation at the stage of seed formation - stopping irrigation at the flowering stage - stopping irrigation at the vegetative growth stage - without irrigation), and the following indicators were studied: water need, The weight of the seeds, the percentage of oil in the seeds, and the determination of the Ky coefficient for each of the different stages, the results showed that the highest seed production was in the full irrigation treatment (641.3) kg/ha, followed the treatment of stopping irrigation at the stage of seed formation (629) kg/ha without There were significant differences, and the percentage of oil in the seeds was significantly higher when treated without irrigation (29.11%). The results also showed the lowest value of the crop response coefficient for deficit irrigation Ky was (0.079) when treating stop irrigation at the stage of seed formation, which is the best treatment for safflower cultivation. The lowest production in the treatment of stopping irrigation at the growth stage And vegetative, where the study showed that this stage is sensitive to lack of water, followed by the flowering stage.
Keywords: Safflower; Stop Irrigation; Water Requirement; Oil Percentage.; Coefficient Ky